Menopausal hormone therapy and risk factors of breast cancer development - A E Protasova; S V Yureneva; E N Vandeeva (Гинекология, 2017)
The article reviews the literature data of the latest studies and expert conclusions on the relationship between menopausal hormone therapy and the risk of developing breast cancer.